HUBUNGAN KETUBAN PECAH DINI DENGAN KEJADIAN SEKSIO SESARIA DI RSUD ULIN BANJARMASIN PERIODE JUNI-JULI 2014 - Herla Maulita Surdhawati; Renny Aditya; Farida Heriyani (Berkala Kedokteran, 2015)
Premature Rupture of Membranes (PROM) is a membranes rupture during before delivery takes. PROM cause a direct contact between the world outside and inside uterus. PROM cause some problems for both mother and fetus, because it should be managed by cesarean section. The purpose of this study is to determine the relationship between PROM with cesarean section in RSUD Ulin Banjarmasin on June to July 2014. This is an observasional analytic study with cross sectional approach. The sample was selectedusingaccidental samplingwith a sample size160,the resultswere analyzedusingchi-square test with confidence interval 95%.The results showed 29 mothers with PROM, then found 15(51.724%)managed by cesarean sectionand(48.275%) samples of vaginal birth. Whilethe131women witha diagnosisinstead ofPROM, 34(25.954%) samples managed bycesareansectionand97(74.046%) samples ofvaginalbirth. Chi-square test showed the value of p=0,006 and odds ratio of 3,056. The conclusion of this research is there are relationship between PROM with cesarean section in RSUN Ulin Banjarmasin on June to July 2014. Keywords: premature rupture of membranes, cesarean section, vaginal birth